Increased expression of surface IgM but not IgD or IgG on human B cells in response to IL-4. - Shields, J; Armitage, R; Jamieson, B; Beverley, P; Callard, R (1989)
Surface IgM (sIgM) was increased up to 10 times on human tonsillar B cells activated with IL-4. No change was observed for surface IgD, IgG or IgE. Other activators of human B cells, such as TPA, EBV and anti-IgM resulted in increased expression of the low-affinity receptor for IgE (CD23), but had no effect on sIgM. IL-4 also increased sIgM expression on prolymphocytic leukaemic (PLL) B cells, whereas TPA significantly reduced the level of sIgM. The effect on sIgM thus seems specific for IL-4, and is consistent with the existence of a unique IL-4-dependent B-cell activation pathway. Preincubation with IL-4 did not 'prime' B cells to proliferate in response to subsequent exposure to anti-IgM, and slightly decreased the response to co-stimulation with IL-4 and anti-IgM. The increase in sIgM expression in response to IL-4, therefore, does not seem to be important for proliferation.